A Novel Chemiluiminescence System Based on Ag(III) Complex Oxidation Sensitized by Rhodamine 6G and the Application for the Determination of Cefazolin Sodium in the Injectable Powder and Human Urine - Sun, Han-Wen; Shi, Sha-Sha; Wang, Juan; Chen, Pei-Yun (Asian Journal of Chemistry, 2012)
A novel chemiluminescence (CL) system for the determination of cefazolin sodium is developed based on the direct chemiluminescence reaction of [Ag(HIO6)2]5--Rhodamine 6G (Rh6G)-cefazolin sodium system in sulphuric acid medium. The possible mechanism of chemiluminescence emission and enhancing effect was discussed. Rhodamine 6G can be oxidized by Ag(III) complex to be its excited form (Rh6G*), which could produce chemiluminescence emission at about 550 nm. Otherwise, Rhodamine 6G can be oxidized by Ag(III) complex to be Rh6G oxide. Cefazolin sodium in acid solution could be oxidized by Ag(III) complex to be its excited form, which could excite Rh6G oxide to be its excited form (Rh6G oxide*), which could produce chemiluminescence emission at about 420 nm. The regression equations of the calibration curves in the range of 4.0 × 10-8-4.0 × 10-6 g/mL can be shown as follows: LgI = 0.0018 C + 1.9848, with a correlation coefficient (R2) of 0.9902. The limit of detection (LOD) was 1.73 × 10-8 g/mL. The proposed method was applied satisfactorily for the determination of cefazolin sodium in the injectable powder and patient urine.